Cu-Catalyzed hydrophosphorylative ring opening of propargyl epoxides: highly selective access to 4-phosphoryl 2, 3-allenols. Issue 80 (19th September 2016) - Shen, Ruwei; Yang, Jianlin; Zhao, Haipeng; Feng, Yu; Zhang, Lixiong; Han, Li-Biao
Abstract : A CuI-catalyzed cross-coupling of propargyl epoxides with P(O)H compounds to produce 4-phosphoryl 2, 3-allenols with excellent selectivity under mild conditions is disclosed. Abstract : A novel CuI-catalyzed cross-coupling of propargyl epoxides with P(O)H compounds is disclosed. The reaction proceeded efficiently under mild conditions to give 4-phosphoryl 2, 3-allenols in good to high yields with excellent selectivity. The utility of the products was demonstrated and a plausible mechanism was also proposed.